The war in Ukraine and its impact on Syria: Humanitarian deterioration and risks of disrupting a volatile status quo - Sinem Adar; Muriel Asseburg; Hamidreza Azizi; Margarete Klein; Mona Yacoubian (Stiftung Wissenschaft und Politik (SWP), 2022)
In Syria, the immediate effects of the war in Ukraine have made an already difficult humanitarian situation even worse. Protracted violence in Ukraine or an expansion of the Ukraine war into a larger NATO-Russia confrontation would endanger multilateral cooperation on conflict management, conflict resolution and humanitarian issues in Syria. Protracted conflict in Ukraine could also disrupt the volatile status quo in Syria, potentially endangering ceasefire agreements, tilting the power balance in favour of Iran and thereby increasing the risk of military escalation between Iran and its antagonists, complicating the fight against ISIS, and endangering cross-border humanitarian aid deliveries. Europeans should attempt to insulate the war in Ukraine from Syria as much as possible, double down on efforts to renew the UN Security Council resolution that allows for humanitarian access to northwest Syria and contribute to the long-term objective of an inclusive regional security architecture.
Keywords: 320